Engineering Resilient Financial Ecosystems: An Autonomic Framework for Zero-Trust Cloud Architecture and Automated Governance - Obbu, Sudheer (International Journal of Computational and Experimental Science and Engineering, 2023)
Global financial institutions increasingly rely on Cloud-Native Platforms (CNPs) to support high-frequency trading (HFT), real-time settlement processing, cross-border transfers, and large-scale customer-facing applications. This accelerated migration introduces architectural and operational risks, particularly as traditional perimeter-based security models fail under the dynamism and scale of modern cloud environments. This research introduces a novel, unified Autonomic Zero-Trust Governance Framework (AZTGF), providing a first-of-its-kind integration of self-governing mechanisms with Cybersecurity Mesh Architecture to secure systemic financial infrastructures. By embedding autonomic mechanisms—self-configuration, self-optimization, self-healing, and self-protection—into the financial data plane, institutions can maintain velocity without compromising security. The framework demonstrates how automated certificate and identity lifecycle systems can proactively mitigate outages, reduce operational overhead, and counteract configuration drift. These contributions collectively advance the capabilities of cloud-native financial infrastructures to withstand emergent threats in complex, distributed environments.